Using Proteus Software-Based Instructional Media to Promote Students’ Achievement in Learning Microcontroller - Sofi Hanif; Deni Listyanto Nur Fauzi; Enjang Ahmad Juanda (Jurnal Revolusi Indonesia, 2021)
Microcontroller has been applied in industries to solve engineering problem, but learning process in some vocational high school still have a limitation to construct instructional media simulation for students. This research aims to investigate the effect of using Proteus software as instructional media on students’ achievement in learning microcontroller. The method that used in this research was quasi-experimental design using non-equivalent control group design.  Instructional media in the experimental group was using Proteus software, while the control group was using Microsoft Power Point. The sample was chosen by purposive sampling technique with 60 participants. Both of experimental group and control group consists of 30 students. The result shows the improvement of students’ cognitive in the experimental group was obtained 0.60 and for the control group was 0.38. The average score of affective aspect in experimental group was 81.67, while control group was 76.29. The average score of psychomotor aspect in experimental group was 82.27, while control group was 75.45. Based on the result Proteus software gives the better effect in improving students’ achievement, so it can be considered as one of an alternative instructional media that can be used in vocational high school.